SAT0718-HPR VALIDATION OF THE DANISH VERSION OF THE BRISTOL RHEUMATOID ARTHRITIS FATIGUE QUESTIONNAIRES. (June 2019) - Primdahl, Jette; Esbensen, Bente Appel; Bech, Bianca; Pedersen, Andreas Kristian; Thurah, Annette de
Abstract : Background: The revised Bristol Rheumatoid Arthritis Fatigue Multidimensional Questionnaire (BRAF-MDQ) and the revised BRAF numerical rating scales (BRAF-NRSv2) are available in 33 languages and are validated in six countries (1), but not yet in Danish. Objectives: To validate the Danish version of the BRAFs. Methods: We surveyed patients with Rheumatoid Arthritis (RA) visiting one of three Danish outpatient clinics. The four-factor structure and internal consistency were explored by factor analysis and Chronbach's α. The fatigue construct validity was tested by Spearman correlations with the SF-36 vitality subscale and the VAS-fatigue. Wider construct validity was tested by correlations with VAS-pain, VAS-fatigue, VAS-global, Hospital Anxiety and Depression Subscales (HADS) and the Health Assessment Questionnaire (HAQ). We asked 120 of the patients to complete the BRAFs before and after their visit in order to be able to explore reliability. Results: A total of 225 patients participated, 69.9% were female, mean (SD) age 59.3(0.87), disease duration 11.11(0.63) years, HAQ 0.71(0.05) and DAS28-CRP 2.55(0.08). The four-factor structure of the BRAF-MDQ and the uni-dimensionality of each of the four subscales were confirmed. Internal consistency for the BRAF-MDQ total was a Cronbach's α of 0.94 and 0.79-0.92 for the four subscales. The correlation coefficients between the BRAF-MDQ and the SF-36 vitality subscale were r=0.75, r=0.65 and r=0.74 for the anxiety and depression subscales of the HADS, respectively and r=0.62, r=0.73 and r=0.62 to VAS-pain, VAS-global and HAQ, respectively. Intra Class Coefficient for agreement was 0.995. The Bland-Altman plot showed a mean difference of 1.9 and a variance of 9.8 (-6.8 to 3.0) for BRAF-MDQ with 95% confidence interval. The correlation coefficients for the BRAF-NRS subscales and the subscales of the BRAF-MDQ, the SF-36 vitality subscale and the VAS-fatigue ranged between 0.57-0.93, 0.54-0.68 and 0.66-0.82, respectively. Conclusion: The Danish version of the BRAF-MDQ identifies the same four aspects of fatigue as the original version, showed good internal consistency, moderate-good construct validity reflected by similar correlations to the SF-36 vitality subscale, HADS, HAQ and VAS for pain, fatigue and global health as the original UK-version and good reliability. The BRAF-NRS had moderate construct validity. The Danish BRAFs are considered valid and reliable for identifying aspects of fatigue among Danish patients with RA. References: [1] Hewlett, S; Kirwan J, Bode C, et al. (2018): The revised Bristol Rheumatoid Arthritis Fatigue measures and the Rheumatoid Arthritis Impact of Disease scale: validation in six countries. Rheumatology 57:300-308. Disclosure of Interests: Jette Primdahl: None declared, Bente Appel Esbensen Speakers bureau: For Pfizer, Bianca Bech: None declared, Andreas Kristian Pedersen: None declared, Annette de Thurah: None declared